Sources That Serve to Correction of Negative Changes in Preschooler Behavior - Choriyeva Feruza Amrullayevna (Genius Publishing Group, 2022)
The article highlights the most important manifestations and features of negative changes occurring in the behavior of preschoolers
Keywords: Child; behavior; negative changes; psychological and physiological